Acarbose versus orlistat in weight management of infertile women with polycystic ovarian syndrome: a prospective randomized controlled trial - S., Afrin; S., Ishrat; J., Banu; I., Jahan; S. A., Ansary; K., Nasreen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Polycystic Ovarian Syndrome (PCOS) affects about 4 to 12% of women worldwide. PCOS is the most common cause of anavulation in infertile women. The endocrine dysfunction of PCOS is aggravated by obesity. Weight management is the first line treatment of this condition. In this study, we tried to compare acarbose versus orlistat in weight management of infertile women with polycystic ovarian syndrome. The aim of this study was to compare the effects of acarbose and orlistat in weight management of infertile polycystic ovarian syndrome women. Methods: This open label randomized controlled trial study was conducted in the Department of Reproductive Endocrinology and Infertility, BSMMU, Dhaka, Bangladesh. The study period was 1 year from July 2019 to June 2020. A total of 32 obese infertile women with PCOS were included in the study and randomized to two treatment arms: acarbose 100 mg tds for 3 months and orlistat 120 mg tds for 3-months. Results: The response of adequate (>10%) weight reduction with acarbose was 67% of that with orlistat. The side effects with acarbose were 15% of that with orlistat. Acanthosis nigricans was reduced in 18.8% (n=3/16) of those receiving acarbose.Menstrual cycle regularized in 37.5% (n=6/16) in experimental (acarbose) group and in 18.8% (n=3/16) in control (orlistat) group. Conclusions: The therapeutic potential of acarbose in reducing weight was relatively less than orlistat in obese infertile PCOS women.